Vision Based Interface in Human Computer Interaction - Aditya Verma; Ankita Verma (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This paper provides information on Human Computer Interaction, it actually means that, its present use in the world of technology and its importance in the tech- savvy world of today. The paper goes through the various types of interaction that can take place between a human and a computer, the technicalities of the same, and the future scope of each interface. We always want a path of communication which is fast, is efficient and is user friendly which gives us maximum output and good performance consistently. Vision based interface between human and computer is studied in detail. It can be stated as the most popular types of interaction between human beings and computers. Vision based interaction in HCI makes use of four main techniques; gesture recognition, eye movement recognition or tracking, head tracking and facial expressions recognition and judgement. Analysis for their usage in practical systems has been made. This is the most worked upon area is the vision based hand gesture recognition which has been discussed in this paper. The present studies and key findings in this area have been listed and its future scope and utility has also been discussed in this paper.
Keywords: HCI; Human Computer Interaction; Science; AI; Vision Based